High Plasma Levels of Protein C Activity and Antigen in the Nephrotic Syndrome - Mannucci, Pier Mannuccio; Valsecchi, Carla; Bottasso, Bianca; D'Angelo, Armando; Casati, Stefano; Ponticelli, Claudio (Thrombosis and Haemostasis, 1986)
Low plasma levels of antithrombin III due to excessive urinary loss are thought to be the cause of thrombotic complications in patients with the nephrotic syndrome. To see whether protein C (PC), another antithrombotic protein, is also reduced in plasma by the same mechanism, plasma and urinary protein C were determined in 24 patients with nephrotic syndrome and no thrombotic complication, and compared to plasma and urinary antithrombin III. Twenty patients (83%) had high plasma levels of protein C activity (mean ± SD 157 ± 41 U/dl) and antigen (158 ± 41). Even though measurable amounts of PC antigen were found in the urines of all but two patients the urinary loss of protein C relative to its plasma concentration was about 40 times lower than that of antithrombin III. High protein C might help to counteract hypercoagulability in nephrotic syndrome.
Keywords: Protein C; Antithrombin III; Nephrotic syndrome